Features of Epidemiology of Hepatitis A in the Region with the Selective Strategy of Vaccination of the Population - T. A. Bayanova; N. A. Lihanova; N. A. Kravchenko; M. O. Potapova; L. P. Ignatieva; I. G. Zhdanova- Zaplesvichko; A. D. Botvinkin (Эпидемиология и вакцинопрофилактика, 2019)
Hepatitis A (HA) is one of the most widespread intestinal infections. At present, selective and planned vaccination strategies against HA are used in different regions of the Russian Federation. The goal is to characterize the peculiarities of the manifestation of the epidemic process of HA at the regional level before and after the start of selective vaccination of the population. Materials and methods. A descriptive retrospective epidemiological study on the materials of the Irkutsk region for 1955–2017 was conducted. The incidence in the years before and after the start of vaccination were compared (2003). Municipalities with different incidence of HA were compared by the nature of water sources, bacteriological and chemical indicators of water.  Resutls. Long-term movement of the incidence was divided into three periods. In 1955–1980 there was a growth trend, then the incidence decreased until 2005, after which it stabilized (annual average growth rates + 2.4%, – 2.5%, – 0.2%). Until 1992, the incidence exceeded 100 per 100 thousand population. After 2003, 1-7 thousand people were vaccinated per year (no more than 0.3% of the total population). The total number of vaccinated people for 2003–2017 exceeded 30 thousand (1.3%). A weak correlation was observed between the number vaccinated people and HA incidence in the following year (ρ = 0.154, p >  0.05). After 2005, the incidence did not exceed 10 per 100 thousand; the structure of morbidity changed due to an increase in the proportion of children and the rural population. Seven high-risk and moderate-risk areas for HAV were identified, which had higher ranks in terms of bacteriological indicators of drinking water compared to areas with low incidence. The relationship between the characteristics of water supply sources and the HAVincidence rate in these groups of areas (х² = 2,527 р = 0.471) was identified.  Conclusion. The results of the study are in favor of the need to move from a selective to a planned strategy for vaccinating the population against HAV in rural areas, where it is not possible to quickly organize the supply of drinking water of guaranteed quality to the population.